2019
DOI: 10.3389/fimmu.2019.00160
|View full text |Cite
|
Sign up to set email alerts
|

The Megalocytivirus RBIV Induces Apoptosis and MHC Class I Presentation in Rock Bream (Oplegnathus fasciatus) Red Blood Cells

Abstract: Rock bream iridovirus (RBIV) causes severe mass mortality in Korean rock bream (Oplegnathus fasciatus) populations. To date, immune defense mechanisms of rock bream against RBIV are unclear. While red blood cells (RBCs) are known to be involved in the immune response against viral infections, the participation of rock bream RBCs in the immune response against RBIV has not been studied yet. In this study, we examined induction of the immune response in rock bream RBCs after RBIV infection. Each fish was injecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 55 publications
2
26
0
Order By: Relevance
“…It has been reported that caspase-3 is significantly up-regulated in the late phase of RBIV infection in the liver of rock bream [16]. Apoptosis-related proteins including CASP6, CASP9, and Fas in red blood cells were up-regulated in proteomic profiling [39]. Expression level of CASP3 in rock bream blood cells infected with RBIV is increased significantly at 6 hpi ( Figure 5B).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…It has been reported that caspase-3 is significantly up-regulated in the late phase of RBIV infection in the liver of rock bream [16]. Apoptosis-related proteins including CASP6, CASP9, and Fas in red blood cells were up-regulated in proteomic profiling [39]. Expression level of CASP3 in rock bream blood cells infected with RBIV is increased significantly at 6 hpi ( Figure 5B).…”
Section: Discussionmentioning
confidence: 72%
“…It is known that fish erythrocytes are involved in immune responses such as chemokine signaling pathway, platelet activation, and T cell receptor signaling pathway [38]. In proteome study of Jung et al [39], apoptosis-, MHC I-, and spliceosome-related pathways in rock bream RBCs were up-regulated, and antiviral mechanisms were down-regulated in the response to RBIV infection. In recent years, more evidence has emerged that platelet and their activation state can modulate innate and adaptive immune responses [40].…”
Section: Discussionmentioning
confidence: 97%
“…The outcomes indicated that A. hydrophila infection could up-regulated four gene's expressions (P53, Fas, LRDD, and caspase 8) which were closely related with the death receptor apoptosis pathway, indicating that A. hydrophila infection could activate Fas-related death receptor apoptosis pathway. Interestingly, the Fas and caspase 9 genes of apoptosis-related pathways were the most over-expressed in RBCs of rock bream infected with a megalocytivirus [46].…”
Section: Discussionmentioning
confidence: 99%
“…RBC apoptosis plays an important role also in the mechanism of antiviral immunity and inhibition of RBIV replication in infected fish O. fasciatus. Proteomic analysis of these cells showed an increase in expression of many proteins associated with the apoptosis pathway: CASP6 (caspase 6), CASP9 (caspase 9), and FAS (Fas cell surface death receptor) (16). Most likely, through their activity related to processing and presentation of antigen involving MHC I molecules and the pathway associated with apoptosis, these cells induce the activity of cytotoxic T cells (CD8 + ) and the release of perforin and granzyme, which are the main factors of the mechanism of cytotoxicity and apoptosis of an infected and antigen-presenting cell in the context of MHC I (16).…”
Section: Rock Bream Iridovirusmentioning
confidence: 99%
“…Moreover, erythrocytes of Osteichthyes are probably involved in the immune response as the antigen-presenting cells (APCs), via major histocompatibility complex (MHC) class II antigens, and they can contribute to formation of immune synapse with T cells and NK (natural killer) cells ( 15 ). In Osteichthyes, erythrocytes have been shown to participate in anti-infection immunity against viruses ( 4 , 6 , 9 11 , 16 , 17 ), bacteria ( 13 ), and fungi ( 18 ).…”
Section: Introductionmentioning
confidence: 99%